Proses Pembuatan Simple Dress Dengan Menggunakan Variasi Teknik Tucking - Ariyana Damayanti; Vivi Yulia Agustina (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2023)
Tucking techniques are rarely used in making clothes, designers prefer to follow today's fashion trends, tucking manipulation techniques are able to change ordinary fabrics into 3-dimensional shapes, the purpose of this study is to be able to find out the finished results of making tucking techniques and to be able to find out the finished results of making simple dresses using variations of tucking techniques. The method used is the R & D method, to produce products and test the effectiveness of these products. The author has tested the tucking technique using 3 materials, namely satin, cotton, and balotelli fabric, as well as the size of folds and between folds 1.5 cm: 1.5 cm, 2 cm: 1 cm and 2 cm: 2 cm, trials have been validated to ask for assessments and suggestions related to materials and crease sizes that are suitable to be applied in making tucking, Balotelli material and the size of folds and folds 1.5 cm : 1.5 cm get the best value from the 4 validators. The process of making tucking to look neat must pay attention to the crease used with an accurate size, ensure the seam is straight, and ensure the sewn fold is ironed until slippery before sewing on the horizontal line.